APPLYING THE DISCOVERY LEARNING TO IMPROVE LEARNERS’ READING COMPREHENSION THROUGH ONLINE DICTIONARY APPLICATION - Adetya Norizkyka (Universitas Achmad Yani Banjarmasin, 2020)
Discovery learning approaches, in particular, are designed to engage students in inquiry through which, guided by the teacher and materials, they